Silverleaf whitefly-resistant common beans: an investigation of antibiosis and/or antixenosis - Braga dos Santos, Thais Lohaine [UNESP]; Lopes Baldin, Edson Luiz [UNESP]; Ribeiro, Leandro do Prado; Souza, Camila Moreira de [UNESP]; Bueno, Nadia Maebara [UNESP]; Silva, Ivana Fernandes da [UNESP] (Inst Agronomico, 2020)
The silverleaf whitefly Bemisia tabaci biotype B is one of the most important sucking pests of common bean, which causes severe damages and requires frequently synthetic insecticides spraying to protect crop productivity. The use of common bean cultivars resistant to whitefly attack is an important strategy within an integrated pest management (IPM) program. The biological development of B. tabaci confined to 17 bean genotypes was evaluated in greenhouse trials to verify the occurrence of antibiosis. Whitefly adults were released on plants of these genotypes to oviposit, afterward the incubation period of eggs, nymphal period, complete development period (egg-adult), and viability of the silverleaf whitefly nymphs were recorded. As main results, genotype CHIP 300 prolonged the developmental period from egg to adult (similar to 10 days) and BRS Estilo, Arcelina 4, IPR Garca, Tybata, CHIP 300, IPR Eldorado, H96A102-1-1-1-52, SCS-202-Guara and CHIB 06 caused nymphal mortality, suggesting high levels of antibiosis and/or antixenosis. These genotypes may be helpful in common bean breeding programs aimed at developing commercial cultivars resistant to B. tabaci biotype B.
Keywords: antibiosis; host plant resistance; Phaseolus vulgaris L.; Bemisia tabaci biotype B